Seminal Plasma Modifies the Transcriptional Pattern of the Endometrium and Advances Embryo Development in Pigs - Martinez, Cristina A.; Cambra, Josep M.; Parrilla, Inmaculada; Roca, Jordi; Ferreira-Dias, Graça; Pallares, Francisco J.; Lucas, Xiomara; Vazquez, Juan M.; Martinez, Emilio A.; Gil, Maria A.; Rodriguez-Martinez, Heriberto; Cuello, Cristina; et al. (Frontiers in Veterinary Science, 2019)
Background: Seminal plasma (SP) promotes sperm survival and fertilizing capacity, and potentially affects embryo development, presumably via specific signaling pathways to the internal female genital tract. Objectives: This study evaluated how heterologous SP, infused immediately before postcervical artificial insemination (AI) affected embryo development and the transcriptional pattern of the pig endometria containing embryos. Materials and Methods: Postweaning estrus sows (n= 34) received 40-mL intrauterine infusions of either heterologous pooled SP or Beltsville Thawing Solution (BTS; control) 30 minutes before AI of semen extended to 10% of homologous SP. Embryos (all sows) and endometrium samples (3 sows/group) were removed during laparotomy 6 days after the infusion of SP or BTS to morphologically evaluate the embryos to determine their developmental stage and to analyze the endometrial transcriptome using microarrays (PORGENE 1.0 ST GeneChip array, Affymetrix) followed by qPCR for further validation. Results: Embryo viability was equal between the groups (~93%), but embryo development was significantly (P<0.05) more advanced in the SP-treated group compared to control. A total of 1,604 endometrium transcripts were differentially expressed in the SP group compared to the control group. An enrichment analysis showed an overrepresentation of genes and pathways associated with the immune response, cytokine signaling, cell cycle, cell adhesion, and hormone response, among others. Conclusions: SP infusions prior to AI positively impacted the preimplantation embryo development and altered the expression of the endometrial genes and pathways potentially involved in embryo development.